A model for scholarship of engagement institutionalization and operationalization - Hart, C.; Daniels, P.; September-Brown, P. (South African Journal of Higher Education, 2023)
Transformation policies have been a high priority for governments globally, regionally, and nationally to address past inequalities. Higher Education Institutions (HEIs) are the critical stakeholders that ensure societal transformation. This requires HEIs to reimagine community engagement, with a necessary role-shift from Mode 1: provider of disciplinary knowledge to Mode 2: distributor of knowledge to broader society through engagement and research that is inclusive and impactful. In this article, we present an adapted version of Boyer’s Scholarship of Engagement (SoE) model, to assist HEIs with the institutionalization and operationalization of engaged scholarship, inclusive of some factors and examples to consider for the process. The operationalization of the model helps HEIs to progress toward assessing their SoE effectiveness and, ultimately, their Societal Impact (SI) contribution, to transform society, responsively and responsibly.